Proceedings of the Workshop on Communication by Gaze Interaction 2018
DOI: 10.1145/3206343.3206344
|View full text |Cite
|
Sign up to set email alerts
|

A Fitts' law study of click and dwell interaction by gaze, head and mouse with a head-mounted display

Abstract: Gaze and head tracking, or pointing, in head-mounted displays enables new input modalities for point-select tasks. We conducted a Fitts' law experiment with 41 subjects comparing head pointing and gaze pointing using a 300 ms dwell (n = 22) or click (n = 19) activation, with mouse input providing a baseline for both conditions. Gaze and head pointing were equally fast but slower than the mouse; dwell activation was faster than click activation. Throughput was highest for the mouse (3.24 bits/s), followed by he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(47 citation statements)
references
References 15 publications
3
43
0
1
Order By: Relevance
“…Our findings confirm the findings from Qian et al [37] and Hansen et al [13] where they reported that head input outperforms gaze. Blattgerste et al [2], however, reported that gaze was much faster than head input.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our findings confirm the findings from Qian et al [37] and Hansen et al [13] where they reported that head input outperforms gaze. Blattgerste et al [2], however, reported that gaze was much faster than head input.…”
Section: Discussionsupporting
confidence: 93%
“…This suggests that 3D vs. 2D is of importance for gaze but not for head interaction. The difference between the gaze throughput reported herein and the throughput found previously [13] is most likely due to the equipment used, since they had identical 2D set-ups. Future study is needed, for example, comparing 2D vs. 3D interfaces, motion vs. static background and targets in head space vs. targets in world space.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations